A Review of Patricia Leavy's "Spark" - Dwyer, Rachael (Art/Research International: A Transdisciplinary Journal, 2019)
Patricia Leavy’s latest novel, Spark, takes us on a journey to the wild landscapes of Iceland, alongside a diverse group of characters described as some of the world’s greatest thinkers. Through their discussions, debates, conversations over shared meals and sightseeing adventures, we explore some of the most pressing issues facing humanity, by considering what it means to think, question and research. Spark presents academic ideas at their most accessible, and Leavy’s artful writing shows us how fiction can not only communicate research ideas, but also has the power to change hearts and minds.